Natural selection and sports: an approach to the study of morphological evolution of elite athletes - Carvajal Veitía, Wiliam (Annals of Anthropology, 2013)
This article presents a detailed analysis of concepts described as “universal expansion of body types”, “morphological optimization”, and “selective pressure”. Fundamental base of this analysis rests in the article “Morphological evolution of athletes over 20th century: causes and consequences” published in Sports Medicine in 2001. The matter about secular evolution has been discussed by different magazines specialized in anthropology, but scarcely ever in sports sphere, where morphological changes have been reported take place more quickly due to a group of social, biological and environmental events, among them globalization, better financial incentives, more qualified tournaments, etc. The author’s idea is proposing an integral vision pattern about all concepts that define Homo Olimpicus’s Morphological Evolution (me). With the purpose to analyze the me phenomenon, the author takes Cuban sports population as example, which constitutes a paradigm of an underdeveloped country with high sports results in world and olympic events.